The relevance of lean thinking to sustainable improvement of public office buildings in Nigeria - Adeyemi, Adegbenga; Kasim, Rozilah; Martin, David (Medwell Journals, 2017)
This study looked into the relevance of lean thinking, particularly the application of muda as a supplement to the sustainable improvement diagnosis technique of existing office buildings, for a fuller assessment of user's requirement in Nigeria. The impact of muda as related to the triple bottom line of sustainable development on perceived job productivity and design features was estimated from end-user's perspective, using diagnostic POE as data acquiring tool while the confirmatory analysis was done through AMOS, SPSS and MS Excel to explain the relationship between the different variables. The findings showed that muda is inherent in public office buildings and it has highly significant causal effects of 0.66 and 0.76, respectively on perceived job productivity and design features; it also has strong effect sizes of 44 and 58% in explaining both their variances, respectively. The result revealed that users require more improvement in facilities as against spatial plan and structures while there is a medium and positive correlation of 0.48 between perceived job productivity and design features implying that the improvement of one will consequently lead to the improvement of the other. The study concludes that lean thinking is relevant to building improvement and could serve as good supplement to the current improvement diagnosis of existing public office buildings but not as a substitute since data were only collected from users who are not able to provide the required technical data that would otherwise warrant use of equipment.